ON CENTRALIZERS OF PRIME GAMMA RINGS - Shaker, Heba (Iraqi Journal of Science, 2024)
In this paper , we introduce some results in a prime Γ-ring M with centralizerwhich is related to the quotient Γ-ring Q of M, and prove our main result; Let Mbe a prime Γ-ring with char M ≠ 2, U a non-zero right ideal of M and T1 and T2 twonon-zero centralizers of M. If T1T2(U) = (0), then there exists two elements p, q of Qsuch that qΓU = (0) and pΓU = (0).